MAINTENANCE AS A TOOL FOR INCREASING THE EFFICIENCY OF CHEMICAL-TECHNOLOGICAL PROCESS - Branská Lenka; Pecinová Zuzana; Paták Michal (Vilnius Gediminas Technical University, 2016)
Reliability, flexibility and speed belong among particularly valued parameters of contractor. In manufacturing companies, the achievement thereof is significantly limited by the reliability of production equipment. The aim of the article is to analyse an applied production equipment maintenance system with heavily utilized production equipment, and to define guidelines for its improvement. A content analysis of information obtained in a primary qualitative research and a comparison with theoretical approaches made it possible to define an adequate combination of various types of maintenance, including methods and tools that are not primarily intended for the examined type of manufacturing processes.
ÚDRŽBA JAKO NÁSTROJ ZVYŠOVÁNÍ VÝKONNOSTI CHEMICKO-TECHNOLOGICKÉHO VÝROBNÍHO PROCESU
Keywords: Maintenance; efficiency; chemical industry; production; production equipment; Údržba výrobního zařízení; chemický průmysl; výrobní proces; výrobní zařízení